O impacto das aposentadorias precoces na produç\~ao e na produtividade dos trabalhadores brasileiros - Luis Henrique Paiva; Leonardo Alves Rangel; Marcelo Abi-Ramia Caetano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Brazil is one of thirteen countries in the world whose social insurance system offers a pension based solely upon length of contribution, with no age requirement. This kind of benefit allows contributors to have access to pensions at relatively young ages (here defined as before 60 years old for men and 55 years old for women). The Brazilian legislation does not prevent pensioners from continuing to work and therefore it does not necessarily produce any impacts on labour market participation and productivity. However, what is the real impact of early access to pensions on the labour market? Does the economy lose in production and/or productivity when people have such early access to pensions? Based on data from the Brazilian Institute of Geography and Statistics' National Household Sample Survey (Pnad), the authors apply a logistic model to measure if (and how much) early access to pensions decreases the probability of beneficiaries continuing to work. They also deploy two other strategies (Oaxaca-Blinder decomposition of wage differentials and propensity score weighting) to evaluate whether there is a decrease in productivity among pensioners that continue to work. Conservative estimates suggest a loss of 0.6 per cent of gross domestic product (GDP) per year as an effect of early access to pensions. The most significant effect of early pensions would be on the reduction of work among beneficiaries (0.5 per cent of GDP). There is also an additional effect on reduction of productivity, of 0.1 per cent of GDP.
Keywords: H55; J21; J14; 330; early pensions; production; productivity